2012
DOI: 10.3758/s13423-012-0349-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of verbal short-term memory in task selection: How articulatory suppression influences task choice in voluntary task switching

Abstract: The roles of verbal short-term memory (vSTM) in task selection and task performance processes were examined when individuals were asked to voluntarily choose which of two tasks to perform on each trial randomly. Consistent with previous voluntary task-switching (VTS) research, we hypothesized that vSTM would support random task selection by maintaining a sequence of previously executed tasks that would be used by a representativeness heuristic. Furthermore, because using a representativeness heuristic requires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…In similar applied conditions, task switching appears to be reduced when the overall mental workload of the task ensemble is increased (e.g., Gutzwiller et al, 2014;Sebok et al, 2015). These results also agree with results from the more basic voluntary task switching literature, which considers simple cognitive tasks rather than complex task performance (e.g., Demanet, Verbruggen, Liefooghe, & Vandierendonck, 2010;Weywadt & Butler, 2013).…”
Section: Individual Differences In Executive Attentionsupporting
confidence: 90%
“…In similar applied conditions, task switching appears to be reduced when the overall mental workload of the task ensemble is increased (e.g., Gutzwiller et al, 2014;Sebok et al, 2015). These results also agree with results from the more basic voluntary task switching literature, which considers simple cognitive tasks rather than complex task performance (e.g., Demanet, Verbruggen, Liefooghe, & Vandierendonck, 2010;Weywadt & Butler, 2013).…”
Section: Individual Differences In Executive Attentionsupporting
confidence: 90%
“…It could be argued that the reduction of prediction effects in the SP group was the consequence of larger cognitive burden in the syllable production secondary task, relative to the tongue tapping and syllable listening secondary tasks. Nevertheless, previous studies revealed that articulatory suppression and tapping do not differ in the level of disruption they entail in several non-linguistic cognitive tasks such as digit size judgment tasks 34 and task switching 35 , 36 , suggesting that those secondary tasks do not drastically vary in the amount of cognitive load they imply. Furthermore, the only difference between the syllable production and tapping tasks in the present study was in the linguistic status of the production (being a syllable or a noise), which also indicates that the cognitive load imposed by those secondary tasks was similar.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, not only procedural effects but also memory-based effects and individual differences have been found. VSR is decreased, and conversely repetition bias increases, under working memory load conditions (e.g., Demanet, Verbruggen, Weywadt & Butler, 2013). Differences in VSR have been found for certain populations, for example, VSR is lower for older adults than for young adults (Terry & Sliwinski, 2012), and also lower for individuals with high level of autistic traits (Poljac, Poljac, & Yeung, 2012).…”
Section: Discussionmentioning
confidence: 99%